2010
DOI: 10.2165/11536600-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modelling of Roflumilast and Roflumilast N-Oxide by Total Phosphodiesterase-4 Inhibitory Activity and Development of a Population Pharmacodynamic-Adverse Event Model

Abstract: Covariate effects have a limited impact on tPDE4i. There was a general association between tPDE4i and the occurrence of common AEs in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 43 publications
(79 reference statements)
4
58
0
2
Order By: Relevance
“…Furthermore, the modelling results suggest that PDE4 inhibitors carry the potential to keep HbA 1c at starting levels in db/db mice based on the estimated EMAX of 1. As the estimated PDE 50 of 27.1 in db/db mice is approximately 27-fold higher than the tPDE4i of 1.03 in humans at the effective dose of 500 μg [30], db/db mice seem to require higher exposures for efficacy than humans. This should be considered in the translation of results from mice to humans.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the modelling results suggest that PDE4 inhibitors carry the potential to keep HbA 1c at starting levels in db/db mice based on the estimated EMAX of 1. As the estimated PDE 50 of 27.1 in db/db mice is approximately 27-fold higher than the tPDE4i of 1.03 in humans at the effective dose of 500 μg [30], db/db mice seem to require higher exposures for efficacy than humans. This should be considered in the translation of results from mice to humans.…”
Section: Discussionmentioning
confidence: 88%
“…28). A thorough analysis of the pharmacokinetics of these two and their variability, as they relate to contribution to activity, has been done (Lahu et al, 2010). In this analysis the following equation was used:…”
Section: Procainamidementioning
confidence: 99%
“…This approach might carry the advantage of being able to discriminate between different shapes of PK profiles and their effect on PD end points. However, it has been demonstrated that tPDE4i is a suitable measure to describe the relation between exposure and PD effect 12. Consequently, for this early development project, the model simplification via AUC and tPDE4i was considered to be sufficient to obtain an estimate of human efficacious dose.…”
Section: Discussionmentioning
confidence: 99%
“…Practically, the PDE 50 values obtained from the PK/PD model were linked via the tPDE4i value of 1.03 calculated for the clinically effective roflumilast dose of 500 μg12 to determine the required tPDE4i value of TAK‐648 in humans, using the following equation: trueleft required tPDE 4i TAK 648, human left= PDE 50 TAK 648, mouse · tPDE 4i roflumilast + roflumilast normalN oxide , human PDE 50 roflumilast + roflumilast normalN oxide , mouse …”
Section: Methodsmentioning
confidence: 99%